Policy Brief 17: Protecting border spaces from risks of corruption and criminal behaviours - Jäger, Noémi; Costa, Jacopo; Kassa, Saba (Basel Institute on Governance Policy Briefs, 2026)
Border spaces are designed to regulate movement and stop illicit trade, yet corruption often allows smuggling and trafficking to continue alongside legitimate commerce. This Policy Brief compares research findings from the port of Rotterdam and the Kapitan Andreevo border checkpoint between Bulgaria and Türkiye to examine how corruption and cross-border crime interact in border spaces. It finds that stronger border controls, enhanced technology and new regulations do not necessarily suppress crime. Such interventions can produce unintended consequences, including new opportunities and incentives for corruption. Criminal actors adapt by changing both corruption and concealment strategies to avoid detection and protect their profits. The brief sets out five recommendations for designing anti-corruption and border security reforms that anticipate this adaptation and evolution rather than being undermined by it. About this Policy Brief This publication is part of the Basel Institute on Governance Policy Brief series ISSN 2624-9669. You may freely share or republish it under a Creative Commons BY-NC-ND 4.0 licence. This publication was written as part of the FALCON (Fight Against Large-scale Corruption and Organised Crime Networks) project. FALCON is funded under the European Union’s Horizon Europe Framework Program Grant Agreement ID 101121281. The Basel Institute on Governance, as an associated partner without the right to receive funds directly from the European Research Executive Agency, has received funding from the Swiss State Secretariat for Education, Research and Innovation (SERI). The contents of this document are the sole responsibility of the authors and do not necessarily reflect the views of the European Union, the European Research Executive Agency or SERI.